카메라 프로젝트 언어활동이 유아의 언어능력과 창의성에 미치는 영향 - 양진희(Jin-Hee Yang) (한국콘텐츠학회 논문지, 14(12), 2014)
본 연구의 목적은 카메라 프로젝트 언어활동이 유아의 언어능력과 창의성에 미치는 효과를 알아보는데 있다. 본 연구의 대상은 5세 유아 46명(실험집단 23명, 통제집단 23명) 이었다. 본 연구에서는 실험집단 유아들을 대상으로 10주 동안 주 1회씩 카메라 프로젝트 언어활동을 실시하였으며, 통제집단 유아에게는 실험집단의 처치가 진행되는 동안 생활주제에 따라 유치원 교육활동 지도 자료집에 기초하여 일반적인 언어활동을 진행하였다. 연구결과, 첫째, 유아의 언어능력에서는 실험집단이 통제집단보다 유아의 어휘력, 언어이해력, 언어표현능력 등 모든 영역에서 긍정적으로 향상되었으며 두 집단 간에 통계적으로 유의한 차이가 있는 것으로 나타났다. 둘째, 유아의 창의성에서는 실험집단이 통제집단보다 유아의 유창성, 융통성, 독창성, 상상력 등 모든 영역에서 긍정적으로 향상되었으며 두 집단 간에 통계적으로 유의한 차이가 있는 것으로 나타났다. 이러한 결과는 카메라 프로젝트 언어활동이 유아의 언어능력과 창의성 향상에 긍정적인 영향을 미쳤음을 의미한다. The purpose of this study was to examine the effects of camera project language activities on verbal skills and creativity of preschoolers. The subjects for this study were 46 five-year-olds(23 in the experimental group and 23 in the control group). The experimental group was engaged in camera project language activity. This study was conducted one time a weeks for 10 weeks, total 10 times. The major findings of the study were as follows: First, camera project language activities were effective in boosting verbal skills(vocabulary, verbal comprehension, and verbal expressiveness) of preschoolers. Second, camera project language activities were effective in boosting creativity(originality, flexibility, originality, and imagination) of preschoolers. These results reveal that camera project language activities affect young children’s verbal skills and creativity positively. KCI Citation Count: 3